One-pot oxidation of secondary alcohols to alpha-hydroxy ketones: application to synthesis of oxoaplysinopsin D, E, F, & G - Kulkarni, Akshay S.; Ramesh, Eagala; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2021)
A simple one-pot transformation of secondary alcohols to alpha-hydroxy ketones using pyridinium dichromate (PDC) in DMF has been developed and substrate scope tested with 25 compounds of hydantoin derivatives. Using this method, we have devised a common dihydroxy intermediate and synthesized four natural products oxoaplysinopsins D, E, F, and G for the first time.
Keywords: alpha-Hydroxylation; Hydantoin; Natural product; Oxoaplysinopsin; Retro-aldol

Scalable synthesis of silacyclohexanones and ready access to silicon building blocks - Ramesh, Eagala; Nandawadekar, Laxman D.; Rao, Ramana Sreenivasa; Reddy, D. Srinivasa (Organic Letters, 2023)
A simple and efficient two-step method for the synthesis of silacyclohexanones starting from bis(bromoethylsilanes) using TosMIC is presented. The prepared silacyclohexanones were transformed to nine different heterocycles with silicon incorporation. In addition, the developed methodology was used for the synthesis of a sila analogue of the HDAC6 inhibitor tubastatin A.